Youth Slang and its Influence on the Academic Performance of High School Students - Cantos Pinto, Ana Isabel; Carrera Moreno, Germán Wenceslao (Revista Universidad de Guayaquil, 2025)
This study analyzes the influence of youth slang on the academic performance of high school students in the city of Manta. As communication evolves in response to social and technological needs, slang has become a crucial element in the interaction among young people, reflecting their identity and social dynamics. Using a mixed-methods approach that combines qualitative and quantitative methods, the research included structured questionnaires and semi-structured interviews with teachers. The results reveal that, although youth slang facilitates peer communication, its excessive use in academic contexts can hinder learning and comprehension of content. This study highlights the need for educators to be aware of the slang used by students and to develop strategies to effectively integrate academic language, thereby promoting a more inclusive and effective learning environment. The implications of these findings suggest that education must adapt to the linguistic realities of students to improve their academic performance and communication skills in formal contexts.